KOMUNIKASI ISLAM DAN PERUBAHAN SOSIAL - Muhammad Zakaria Al Anshori (TASÂMUH, 2018)
Social change is a social process experienced by members of society and all elements of culture and social systems, where all levels of people's lives are voluntary or influenced by external elements by abandoning the patterns of life, culture, and social systems long after adjust or use new patterns of life, culture, and social systems. With the existence of social change, of course, Islamic communication has challenges that must be passed and decomposed holistically, by finding and finding alternative solutions for the effectiveness and accuracy of contemporary Islamic communication. Among the concrete problems in the behaviour of social change, for example, modern society today abandons traditional values, has a hedonistic lifestyle and acts spree and so on. Therefore, Islamic communication must lead to handling real problems. This means that Islamic communication activities are efforts to solve or solve the problems of the life of the people and society in the socio-cultural, economic and political fields within the framework of modern society. The form of Islamic communication can be done formally in the activities of individuals in academia, social education institutions and da'wah institutions, and can also be done non-formally by individuals in the social life of the community.